Pengaruh Locus Of Control Terhadap Penguasaan Konsep Mahapeserta Didik Pendidikan Dokter-Universitas Islam Sumatera Utara - Zaim Anshari (Universitas Islam Sumatera Utara, 2021)
The relationship between conceptual understanding and the Locus Of Control, students who have an internal Locus Of Control will tend to have a better concept understanding ability. It is characterized by the emergence of personal awareness of a success or failure and is considered a delayed success so that it will give rise to hard work to achieve successThis research is a correlational study that aims to see the relationship that occurs between the two variables studied. The population in this study were medical education students, The Islamic University of North Sumatra, while the sample was a total of 30 people. The instrument used to collect Locus Of Control data is to use a closed questionnaire that refers to a likert scale of 20 questions. As for the ability to master the concept using a description test which amounts to 5 questions. The data obtained are then analyzed and compared to obtain data that can be used to answer research questions. Based on the results of the questionnaire on the Locus Of Control aspect, students' Locus Of Control ability was distinguished in three categories (high, medium, low) which were dominant with the medium category as much as 43.33% and the high category as much as 40%, while the rest were included in the low category of 16.67%. Then the comparison between the ability of the Locus Of Control and the mastery of concepts can be stated that students with a good Locus Of Control will get good grades as well. This is indicated by the average value of mastery of concepts with a high Locus Of Control is 16 which is not much different from the average value of mastery of concepts with a medium Locus Of Control of 16.54. This shows that the Locus Of Control has a significant effect on the Ability to Master students' concepts.